Heavy metal accumulation capacity of La Totora in the Ite wetland, Tacna – Peru - Atencio Iturry, Ivette Eneida (2017)
Plants develop, due to their biological constitution, vital functions for man, in this situation, aquatic plants prove to be an alternative for the change of the district's ecosystem, so it is necessary to know the capacity to accumulate heavy metals from waters contaminated with tailings. miners. The general objective of the project is to determine the capacity of the reed to accumulate heavy metals in the Ite wetland. In the present research work, samples of reed Thypha spp were collected in plastic containers, sterilized and labeled, the analyzes were carried out in the analytical chemistry laboratory of CERPER - Lima, the results compared in two consecutive years, had values ​​between 0.05 and <2 mg / kg for Pb, 0.04 and <0.02mg / kg for As and 1.83 and 4.97 mg / kg for Zn. Reaching the conclusion that the cattail Thypa spp, presents concentration levels of heavy metals, which are within the permissible levels.